Does Ownership Structure Pay Attention to The Corporate Cash Policy? Evidence in Indonesia Firms - R. Heru Kristanto HC; Mamduh M Hanafi (ETIKONOMI, 2019)
Cash and its use will connect to many things, such as the performance of corporate governance. This empirical research examines the interaction effect of insider ownership, institutional ownership, and independent board toward the influence of cash policy on the firm value. This research using agency theory framework, corporate governance using Indonesia listed firms’ samples over 2001-2017 (197 firms, 3349 observation). Fixed effect dynamic panel regression and regression-moderated analysis used in this research. We show that these results suggest that the insider ownership, institutional ownership, and independent board strengthen the influence of the corporate cash policy on firm’s value. It develops the previous research findings in Indonesia, especially in the implication of cash management from the perspective of agency theory and corporate governance.JEL Classification: G32, L21